Electromagnetic wave polarization state evolution in weakly anisotropic and nonuniform media with dissipation - Bieg, Bohdan; Chrzanowski, Janusz (Photonics Letters of Poland, 2017)
The change of the polarization state of electromagnetic beam propagating in weakly anisotropic and smoothly inhomogeneous media with dissipation is analysed. On the basis of a quasi-isotropic approximation, which provides the consequent asymptotic solution of Maxwell's equation, the differential equation for the evolution of four component Stokes vector is derived. Obtained equation generalizes previous results for the nonadsorbing media and is written in terms of the dielectric tensor of birefringent media with dissipation. The formalism is illustrated by an example of magnetised plasma with dissipation due to the electron collisions. Full Text: PDF References K.G.Budden, Radio Waves in the Ionosphere (Cambridge U. Press 1961). V.I.Ginzburg, Propagation of Electromagnetic Waves in Plasma (Gordon & Breach 1970). Yu.A.Kravtsov, ""Quasiisotropic" Approximation to Geometrical Optics", Sov. Phys. Dokl. 13, 1125 (1969). A.A. Fuki, Yu.A. Kravtsov, and O.N. Naida, Geometrical Optics of Weakly Anisotropic Media (Gordon & Breach, Lond., N.Y. 1997). Yu.A. Kravtsov and Yu.I. Orlov, Geometrical optics of inhomogeneous media (Springer Verlag, Berlin, Heidelberg 1990). CrossRef Yu.A. Kravtsov et al., "Waves in weakly anisotropic 3D inhomogeneous media: quasi-isotropic approximation of geometrical optics", Physics-Uspekhi 39, 129(1996). CrossRef F.De Marco, S.E.Segre, "The polarization of an e.m. wave propagating in a plasma with magnetic shear. The measurement of poloidal magnetic field in a Tokamak", Plasma Phys. 14, 245 (1972). DirectLink S.E.Segre, "A review of plasma polarimetry - theory and methods", Plasma Phys. Control. Fusion 41, R57 (1999). CrossRef M. Born and E. Wolf, Principles of Optics (Pergamon, Oxford 1980). CrossRef B.Bieg et al., "Quasi-Isotropic Approximation of Geometrical Optics Method as Adequate Electrodynamical Basis for Tokamak Plasma Polarimetry", Physics Procedia 62, 102 (2015). CrossRef B.Bieg et al., "Two approaches to plasma polarimetry: Angular variables technique and Stokes vector formalism", Nucl. Instr. Meth. Phys. Res. Sect. A 720, 157 (2013). CrossRef S.E.Segre, "New formalism for the analysis of polarization evolution for radiation in a weakly nonuniform, fully anisotropic medium: a magnetized plasma", J. Opt. Soc. Am. A 18, 2601 (2001). CrossRef